Intention to Use Digital Payment on Traditional Market: Unified Theory Approach - Dian Safitri Pantja Koesoemasari; Mayla Surveyandini; Juvita Ananda Putri; Sahrul Romadhon (LP3M Universitas Putra Bangsa, 2025)
The success of the national cashless action will occur if all levels of society are familiar with and interested in using it, especially at the most basic level, thats a traditional-markets. The theory used to explain is the unified theory of acceptance and use technology (UTAUT). UTAUT is more appropriate to use because it can explain the use of digital payments voluntary and mandatory. The population in this study were merchant in the Pasar Manis Purwokerto, totalling 512 merchants. The minimum research sample based on Isaac and Michael was obtained as many as 220 respondents, while the data processed were 222 respondents. Data were analysed using multiple linear regression. The results of this study can only prove that performance expectancy has a significant positive effect and social influence has a significant negative effect on the intention to use digital payments. These results illustrate that traditional market traders are still in the ‘early adopter’ stage in accordance with one of the supporting theories of UTAUT, namely the technology acceptance model (TAM). Social influence has a negative effect coming from buyers and people around traders not forcing them to use the digital payment.